An exploration of nurses' knowledge, attitudes and intentions regarding restraint use in elderly residential care facilities. Issue 6 (14th May 2022) - Redmond, Liam Gerard; Hyland, Pauline K.; Orr, Patricia Meredith; White, Mark
Abstract: Purpose: In Ireland, there is a regulatory focus on restraint minimisation in elderly residential care facilities. Consistent with this focus, this study aimed to explore and identify the relationship between nurses' knowledge levels, attitudes and intentions regarding physical restraint use in two large Irish elderly residential care facilities. Design: A correlational and cross‐sectional survey design was used to collect data on variables including nurses' education levels, years of experience and intentions toward restraint utilization. Methods: Data was obtained from a sample of 83 nurses in early 2020 via an anonymous, adapted survey measuring knowledge, attitude and intentions. Results: Results showed high knowledge levels, negative attitudes toward restraint implementation, and moderate mean intention scores. A significant positive relationship existed between knowledge and attitudes, with both variables negatively predicting intentions regarding restraint. Education was significant in predicting knowledge and attitudes; however, years of experience reported no such findings. Conclusion: Knowledge and attitudes negatively predict nurses' intentions toward restraint, with attitude being the stronger predictor of intentions. Falls risk caused the greatest variation in intention scores. Clinical Relevance: This research offered a seminal study providing insight into the use of restraints in an Irish context with findings that are in line with international research. It highlights the importance of knowledge and attitudes along with education with understanding intentions to use restraints. Furthermore this research demonstrates a useful instrument in the assessment of nurses' knowledge, attitudes, and intentions in Irish elderly residential care facilities, which can possibly be used in other settings.